THE ORGANOLOGY OF GRAND ANGKLUNG INSTRUMENT IN PADASUKA BANDUNG - Sella, Sella Nurlela; Joko Srimoko, Gandung; Saryanto (Jurnal Penelitian Musik, 2023)
The research method used is determine the organology of Grand Angklung musical instrument in Padasuka, Bandung. Organology which includes physical aspects, namely the basic materials of instruments, shapes, dimensions of construction, methods of manufacture and non-physical aspects, namely functions in music, history, and its distribution. The object of this research is the Grand Angklung musical instrument in Padasuka, Bandung. The research method used is descriptive qualitative research method. The results of this study describe 1) organology which includes physical aspects, (a) the basic materials of the instrument using bamboo and iron, (b) the shape of the long angklung grand instrument with a range of notes like a piano, (c) the size of the grand angklung construction has a length of approx. 3.30 meters with a height of 90 cm, (d) how to make it using electric welding to assemble the frame. 2) organology which includes non-physical aspects, (a) the function of music to accompany a song by having a wider range of tones than other instruments, (b) history before the creation of this instrument, namely the hanging angklung which had problems playing certain songs and the shape of the grand angklung is inspired by YouTube, (c) the spread of this instrument by performing external or internal performances and the studio where it is made is well known to foreign countries. Grand angklung is an innovation in creative angklung creations.